2021
DOI: 10.1159/000515056
|View full text |Cite
|
Sign up to set email alerts
|

Are Demoralization and Insight Involved in Suicide Risk? An Observational Study on Psychiatric Inpatients

Abstract: <b><i>Introduction:</i></b> Several features contribute to determining suicide risk. This study was designed with the aim of evaluating whether insight into illness and demoralization are involved in suicide risk (active suicidal ideation or behavior). <b><i>Methods:</i></b> For this purpose, in a sample of 100 adult psychiatric inpatients, we used the Columbia Suicide Severity Rating Scale to assess suicide risk, the Demoralization Scale for demoralization sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Several studies have demonstrated that illness awareness is associated with increased suicide risk in patients with schizophrenia ( 95 97 ). In a recent study of 100 psychiatric inpatients, Berardelli et al ( 98 ) reported that patients with higher scores on the insight-high dimension had a 1.35 greater odds of having a higher suicide risk, indicating that greater illness insight is involved in suicide risk.…”
Section: Suicide Risk Status In Schizophreniamentioning
confidence: 99%
“…Several studies have demonstrated that illness awareness is associated with increased suicide risk in patients with schizophrenia ( 95 97 ). In a recent study of 100 psychiatric inpatients, Berardelli et al ( 98 ) reported that patients with higher scores on the insight-high dimension had a 1.35 greater odds of having a higher suicide risk, indicating that greater illness insight is involved in suicide risk.…”
Section: Suicide Risk Status In Schizophreniamentioning
confidence: 99%
“…The relevance of psychache in the development of suicidality has progressively been established in studies conducted in both clinical and nonclinical settings (Pompili et al, 2008;Cáceda et al, 2014;Berardelli et al, 2019). Another construct that needs to be mentioned when considering suicidality is hopelessness, a symptom that can be included in the broader syndrome of demoralization, along with feelings of impotence and loss of the meaning of life (Costanza et al, 2020;Berardelli et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%